RESPON PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) TERHADAP DOSIS MIKORIZA DAN FREKWENSI PENYIRAMAN - Sulastri, Yustina Sri; Gusriani, Yunda; Sinaga, Ricci (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study entitled Effect of Mycorrhizal Dosage and Watering Frequency on the Growth of Cocoa (Theobroma cacao L.) Seeds. The purpose of this study was to determine the frequency of watering and the right dose of mycorrhizal fungi in cocoa (Theobroma cacao L.) nursery techniques. In this study using a randomized block design (RBD) consisting of two factors. The first factor is the frequency of watering (P) which consists of 4 levels: P1 = watering once a day, P2 = watering every 3 days, P3 = watering every 5 days and P4 = watering once every 7 days. The second factor was the mycorrhizal dose (M) which consisted of 4 factors: M0 = without mycorrhizal administration, M1 = 25 g mycorrhizal, M2 = 50 g mycorrhizal and M3 = 75 g mycorrhizal. Parameters observed consisted of plant height, stem diameter, number of leaves, leaf area, fresh weight of roots, dry weight of roots, fresh weight of plants and dry weight of plants. The results showed that the treatment of watering frequency significantly increased root wet weight and plant wet weight, but had no significant effect on plant height, stem diameter, number of leaves, leaf area, root dry weight and plant dry weight. Mycorrhizal dose treatment had no significant effect on plant height, stem diameter, number of leaves, leaf area, root wet weight, root dry weight, plant wet weight and plant dry weight. The interaction of watering frequency and mycorrhizal doses had no significant effect on plant height, stem diameter, number of leaves, leaf area, root wet weight, root dry weight, plant wet weight and plant dry weight.